Suitability of Liveable Settlement Concept in Kampung Guji Baru, Jakarta - Eugenia Winny Geraldusi Ailet; Aphrodita Puspateja; Ken Martina Kasiokoen; Aditianata (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2026)
Rapid urbanization in Jakarta has accelerated the growth of settlements, including Kampung Guji Baru, which is categorized as an uninhabitable area. According to the Governor of DKI Jakarta Provincial Regulation No. 90 of 2018, the settlement was designated as a priority location for integrated improvement and underwent restructuring in 2022. Despite its strategic location near the economic center and public transportation, the condition of the settlement still requires further government attention. This study aims to evaluate the suitability of Kampung Guji Baru based on the concept of a livable settlement. The research is intended to identify the community’s main needs and problems while emphasizing the role of community participation. A quantitative descriptive method with a rationalistic approach was applied, using observation and questionnaires with the Guttman scale technique. The findings reveal that the settlement faces several major issues. These include high building density, reaching 185 units per hectare, limited open space, and inadequate infrastructure, such as wastewater management, availability of TPS 3R, and fire protection facilities. Nevertheless, the accessibility of education, health, worship, and public transportation facilities is considered highly suitable, with a percentage of 91.67%. Community participation, however, remains relatively low at 43.51%, primarily due to limited involvement in decision-making and insufficient gender participation. Overall, the assessment of the liveable settlement concept indicates that Kampung Guji Baru achieves a total suitability score of 60.98%. This rating categorizes the settlement as “in accordance,” highlighting the need for continuous improvement to achieve a more sustainable and inclusive living environment.